The Choice of Leg During Pull Test in Parkinson's Disease: Not Mere Chance - Spagnolo, Francesca; Rini, Augusto Maria; Guida, Pietro; Longobardi, Sara; Battista, Petronilla; Passarella, Bruno (Frontiers in Neurology, 2020)
Background: Parkinson’s disease (PD) starts asymmetrically and it maintains a certain degree of asymmetry throughout it course. Once functional disability proceeds, patients can change their dominant hand due to the increased disease severity. This is particularly true for hand dominance, while no studies have been performed so far exploring the behavioral changes of lower limb utilization in PD according to the lateralized symptom dominance. In the current study we aim to track the foot preference of PD patients to respond to the Pull-Test. Methods. Forty-one PD patients having a H&Y scale 2 were recruited. A motor evaluation was performed, including the motor part of the MDS-UPDRS, its axial and lateralized scores (for worse and better side), two Timed Tests and the Pull-Test. The preferred foot (right or left) involved in the step backward was recorded. Thirty-seven healthy controls underwent a motor assessment which included the Pull-Test and the Timed Tests. Both patients and controls were right-handed. To evaluate the relationship between the response to Pull-Test and PD-symptoms, the PD-group was further divided into two groups: 1) PD worse on the right side (PD_RIGHT), and 2) PD worse on the left side (PD_LEFT). Results. Both groups of patients (PD_RIGHT and PD_LEFT) during the Pull-Test shifted significantly their leg use preference toward the opposite side than the worse side: PD_RIGHT used preferentially their left leg (71%) and vice versa (p<0.001). The limb preference shift was especially true for PD_LEFT group that almost invariably used their right, dominant leg to respond to the Pull-Test (95%). Similar results were obtained comparing PD subgroups with controls. Conclusions. This study shows that the limb used to respond to the Pull-Test generally predicts the contralateral side of worse PD involvement. As the disease takes place, it prevails over hemispheric dominance: right-handed patients with left side PD onset and worse lateralization tend to be hyper-right-handers, while right-handed patients with right side PD-onset and worse impairment, tend to behave as left-handers. Lateralization of symptoms in PD is still a mysterious phenomenon; more studies are needed to better understand this association and to optimize tailored rehabilitation programs for PD-patients.